PERTUMBUHAN DAN KEMATANGAN GONAD IKAN WAKONG MERAH (Caesio chrysozona) DI KEPULAUAN BANDA - Munira Munira; Tjameria La Ima; Wita Uswanas (Amanisal: Jurnal Teknologi dan Manajemen Perikanan Tangkap, 2024)
The fusilier fish (Caesio chrysozona) is an abundant fish resource that contributes to the economy of the Banda Islands community. This study aims to examine the growth, gonad maturity level (GML), and gonad maturity index (GMI) of the red fusilier fish landed on the coast of Kampung Baru Village, Banda District, Central Maluku. The study was conducted from July to August 2023. A total of 40 fish were collected, measured for their total length, and weighed for their body weight. After that, the fish were dissected for gonad observation, which was then weighed and determined for gonad maturity levels. The results showed that out of 40 fish, there were 14 male and 26 female fish. The length of the fish ranged from 18 to 24 cm, with body weights for females between 83 and 220 grams, and for males between 79 and 171 grams. The length-weight relationship analysis showed a (b) value for female fish of 3.664 with an ( R2) value of 0.834, while male fish had a (b) value of 1.446 with an (R2) value of 0.273. The length-weight relationship equations for female fish is (W=0.0018 L{3.664}), and for male fish (W=1.7876 L{1.446}). The gonad maturity level (GML) was dominated by GML II for both genders. The gonad maturity index (GMI) varied each month during the study, with the highest GMI for males reaching 3.10% and the lowest at 0.25%, while the highest GMI for females was 2.562% and the lowest was 0.091%.